2003
DOI: 10.1590/s1677-55382003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Racial influence on the prevalence of prostate carcinoma in Brazilian volunteers

Abstract: Purpose: To investigate the prevalence of prostate carcinoma in a sample of volunteers known to have a large proportion of Bantu African ancestors, and the performance of total PSA (tPSA), PSA density (PSAD) and free-to-total PSA ratio (f/tPSA) on the diagnosis.Materials and Methods: A total of 473 volunteers (range: 40 -79 years) were screened for prostate carcinoma. Those with tPSA >2 ng/ml and/or abnormal digital rectal examination were submitted to a transrectal ultrasound-directed biopsy (10 cores). The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
1
23
1
3
Order By: Relevance
“…Thus, patients with low and intermediate Gleason scores had a greater degree of African ancestry, contrary to previous reports of faster PCa progression among black American men (Powell et al, 2010). Furthermore, our analysis showed that patients with rapid PCa growth had a higher European genetic contribution, although several studies have demonstrated that black men are at greater risk of PCa compared to white men, especially in North America (Bouchardy et al, 1991), and present with a more advanced stage at diagnosis (Paschoalin et al, 2003;Coleman et al, 2008;Rebbeck et al, 2013). Our results can be attributed to the high rate of admixture in the Brazilian population resulting from five centuries of interethnic unions between parental groups.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Thus, patients with low and intermediate Gleason scores had a greater degree of African ancestry, contrary to previous reports of faster PCa progression among black American men (Powell et al, 2010). Furthermore, our analysis showed that patients with rapid PCa growth had a higher European genetic contribution, although several studies have demonstrated that black men are at greater risk of PCa compared to white men, especially in North America (Bouchardy et al, 1991), and present with a more advanced stage at diagnosis (Paschoalin et al, 2003;Coleman et al, 2008;Rebbeck et al, 2013). Our results can be attributed to the high rate of admixture in the Brazilian population resulting from five centuries of interethnic unions between parental groups.…”
Section: Discussioncontrasting
confidence: 97%
“…These findings are similar to those of Paschoalin et al (2003), who analyzed the influence of ethnicity on PCa prevalence in northeastern Brazil, demonstrating that patients anthropologically classified as white exhibited 67.5% European, 20.8% African, and 11.7% Amerindian contributions, while in the mixed group, these values were 54.8, 36.3, and 8.9%, and among black participants were 45.3, 45.9, and 8.8%, respectively. Despite the small number of individuals analyzed in our study, the ancestry estimates obtained were close to those reported in the 2010 census by the Brazilian Institute of Geography and Statistics (IBGE 2011).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of prostate cancer in Brazil is higher in Black men compared to White men (12)(13)(14)(15). We studied the influence of race in regard to biochemical recurrence after radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…It was not a randomized, prospective study, and although literate and illiterate men were contemporary and of similar age range, intrinsic differences in their characteristics cannot be fully ascertained. Additionally, data on ethnicity were not available, since such these classifications in the largely multiethnic Brazilian population are difficult to attribute, as previously shown in genetic studies in Brazilian volunteers for prostate screening (29)(30)(31). Another limitation is that income data is not available, but the screening program was targeted to an underprivileged, uninsured population living in rural areas, with all work up and treatment performed by the public health system.…”
Section: Discussionmentioning
confidence: 99%